The establishment of Norway spruce (Picea abies (L.) Karst.) on two mountains in the Åre area - Ek, Lars-Göran (2004)
The general migration model for Norway spruce (Picea abies) suggests that it arrived and established in Sweden along the Bothnian coast about 3500 years ago. Spruce thereafter spread westwards and southwards in Sweden, and it is suggested to have become established in the Scandes mountains about 1300-1600 years ago. Recent macrofossil finds in the Scandes mountains have challenged this theory. Two macrofossils of Norway spruce dated to 11 020 and 10 250 14C yr BP have been found on Mt Åreskutan that is a mountain top in the southwestern Swedish Scandes. The aim of this study was to find out if this early establishment of Norway spruce on Mt Åreskutan could be verified with pollen analysis. Two mires where selected for the study on two adjacent mountains, Årebjörnen and Totthummeln 6,5 km and 3,5 km distant from Åreskutan. The pollen diagrams reveal that Norway spruce was established on these two mountains about 4000 years cal. BP. This much later establishment of spruce on Årebjörnen and Totthummeln compared to Mt Åreskutan show that the establishment of spruce in an area can vary strongly in time plausibly due to differences in local climate and due to competition from already established vegetation. The reason for the absence of spruce pollen from Mt Åreskutan in the Årebjörnen and Totthummeln peat stratigraphies, can be that the population on Åreskutan was to small and the distance between the two mountains and Åreskutan is to long for spruce pollen to be dispersed. Still the establishment on the studied mountains occurred ca 2500 years earlier than postulated by the former model. The stand of Ulmus that can be found on the south side of Totthummeln today has most likely been established during the post glacial temperature optima and is thus a relict that has survived for 7000 years.